SLR Review of the Identification and Dynamics of Push, Pull, and Mooring Factors in Switching Intentions for the Adoption of Sustainable Products - Luki Sri Anggorowati; Ihwan Susila; Kussudyarsana Kussudyarsana (International Journal of Management Science and Information Technology, 2026)
This study aims to explore the dynamics of switching intention in the adoption of sustainable products through an analysis of push, pull, and mooring factors. A bibliometric approach and Systematic Literature Review (SLR) analysis were used to identify and synthesize previous findings, with a focus on literature related to consumer behavior and sustainability. The results of the study indicate that switching intention is influenced by the complex interaction between various interrelated factors. Push factors such as dissatisfaction with conventional products and increasing environmental awareness are the main catalysts in driving consumer switching. On the other hand, pull factors such as innovation, green brand image, and functional benefits contribute to enhancing the appeal of sustainable products. However, mooring factors such as brand loyalty, perceived high prices, and limited access remain major challenges in this transition process. This study also reveals gaps in the literature, such as the lack of integration between the three factors and the limited scope of studies in local and regional contexts. Thus, this study contributes to enriching the literature on sustainable consumer behavior and offers practical implications for developing more effective marketing strategies.